Maternal selenium levels and whole genome screen in recurrent spontaneous preterm birth population: A nested case control study. (October 2021) - Care, Angharad G.; Gupta, Juhi K.; Goodfellow, Laura; Zhang, Ge; Monangi, Nagendra; Belling, Elizabeth; Landero, Julio; Chappell, Joanne; Sharp, Andrew; Alfirevic, Ana; Müller-Myhsok, Bertram; Muglia, Louis J.; et al.
Highlights: Low second trimester maternal selenium levels associate with spontaneous PTB risk. Selenium not sufficiently predictive in the context of personalised medicine. First GWAS using maternal Se levels as continuous data investigating recurrent s PTB. Low maternal Se levels in women with recurrent sPTB associated with variant in FOXN3 gene. Abstract: Objective: To establish if low maternal selenium (Se) was associated with sPTB in women with recurrent sPTB and identify genetic link with maternal Se levels. Design: Nested case-control study. Setting: Tertiary Maternity Hospital. Population: Plasma and whole blood from pregnant women with history of early sPTB/PPROM < 34 +0 and European ancestry were obtained at 20 weeks (range 15–24 weeks). 'Cases' were recurrent PTB/PPROM < 34 +0 weeks and term (≥37 +0 ) deliveries were classified as 'high-risk controls.' Women with previous term births and index birth ≥ 39 weeks were 'low-risk controls'. Methods: Maternal plasma Se measured by ICP-MS was used as a continuous phenotype in a GWAS analysis. Se was added to a logistic regression model using PTB predictor variables. Main outcome measures: Maternal Se concentration, recurrent early sPTB/PPROM. Results: 53/177 high-risk women had a recurrent sPTB/PPROM < 34 +0 weeks and were 2.7 times more likely to have a Se level < 83.3 ppm at 20weeks of pregnancy compared with low-risk term controls (n = 179), (RR 2.7, 95%CI 1.5–4.8; p = .001). One SNP from a non-coding region ( FOXN3 intron variant, rs55793422) reached genome-wide significance level (p = 3.73E −08 ). Targeted analysis of Se gene variant did not show difference between preterm and term births. (χ 2 test, OR = 0.95; 95%CI = 0.59–1.56; p = 0.82). When Se levels were added to a clinical prediction model, only an additional 5% of cases (n = 3) and 0.6% (n = 1) of controls were correctly identified. Conclusions: Low plasma Se is associated with sPTB risk but is not sufficiently predictive at individual patient level. We did not find a genetic association between maternal Se levels and Se-related genes.